2005
DOI: 10.1212/01.wnl.0000166038.67153.9f
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fatty acids and the risk of Parkinson disease

Abstract: These findings suggest that high intake of unsaturated fatty acids might protect against Parkinson disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
153
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(165 citation statements)
references
References 47 publications
8
153
4
Order By: Relevance
“…Moreover, this study showed that switching MUFAs and PUFAs for saturated fats prevented the increase in cholesterol expected from intake of a high-fat diet ( 157 ). In a prospective study of older adults, increased consumption of total fats, MUFAs, and PUFAs was associated with a lower risk of PD ( 158 ).…”
Section: Pdmentioning
confidence: 66%
“…Moreover, this study showed that switching MUFAs and PUFAs for saturated fats prevented the increase in cholesterol expected from intake of a high-fat diet ( 157 ). In a prospective study of older adults, increased consumption of total fats, MUFAs, and PUFAs was associated with a lower risk of PD ( 158 ).…”
Section: Pdmentioning
confidence: 66%
“…All participating patients reported moderate to very good improvement in symptoms. Further, as in Alzheimer's disease, consumption of foods containing increased amounts of essential fatty acids has been associated with a lower risk of developing Parkinson's disease (de Lau et al, 2005).…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…The role that fat plays in PD is most likely related to the type of fat in the patient's diet (De Lau et al, 2005), the patient's HDL/LDL ratio, total cholesterol levels and genetic factors. Ideally, large prospective randomized controlled studies are needed to clarify the associations between fat intake and PD.…”
Section: Nutrients With a Questionable Role In Pd Fatmentioning
confidence: 99%
“…Because of the limited number of patients, the difficulty in adhering to a hyperketonemia diet, and the lack of healthy controls, the authors were not able to rule out a placebo effect. The promising results from this preliminary study suggest that another clinical trial of the ketogenic diet that includes a larger number of patients is warranted.Dietary intake of PUFAs and monounsaturated fatty acids (MUFAs) might influence the risk of PD (Abbott et al, 2003;De Lau et al, 2005). It has been reported in other disease models that PUFA's have anti-inflammatory and neuroprotective properties (Blok et al, 1996;Simopoulos, 1999;Youdim et al, 2000;Kim et al, 2001) and MUFAs are thought to reduce oxidative stress (Colette et al, 2003;Moreno and Mitjavila, 2003).…”
mentioning
confidence: 99%